Monitoring and exposure assessment of nitrate intake via fruits and vegetables in high and low risk areas for gastric cancer - Ghaffari, Hamid Reza (J Environ Health Sci Eng, 2019)
BACKGROUND: Gastric cancer (GC) is the first leading cause of cancer-related deaths in Iran. GC is a multifactorial disease and is caused by the interaction of genetic and environmental factors. The aim of this study was to assess the exposure and risk of nitrate intake through fruits and vegetables (F&V) in high-risk area (HRA) and low-risk area (LRA) of GC in Iran. METHODS: Twenty nine species of F&V were examined for nitrate by reverse-phase HPLC (RP-HPLC) method. Food frequency questionnaire (FFQ) data of 2000 adults participating in Persian cohort were applied to determine consumption patterns of F&V in those areas. A point-estimate daily intake was applied to compare two areas in terms of nitrate intake. Monte-Carlo simulation technique was applied to estimate chronic daily intake (CDI) of nitrate. RESULTS: The results showed that point-estimate daily intake of nitrate for subjects participated in the study was 2.02 ± 1.02 mg kg(−1) day(−1) in HRA and 1.98 ± 1.05 mg kg(−1) day(−1) in LRA. 6.53% of the participants in the HRA, and 5.9% of the participants in the LRA had an unacceptable point-estimate daily intake compared with an acceptable limit of 3.7 mg kg(−1) day(−1) established by FAO/WHO. CDI of nitrate in HRA was 1.94 ± 0.95 mg kg(−1) day(−1) and in the LRA was 1.93 ± 1.06 mg kg(−1) day(−1). CONCLUSION: The results showed that there is no difference between HRA and LRA in terms of nitrate intake through F&V.